Affordable Motion Tracking System for Intuitive Programming of Industrial Robots - Švejda, Martin; Goubej, Martin; Jáger, Arnold; Reitinger, Jan; Severa, Ondřej (Sensors (Basel, Switzerland), 2022)
The paper deals with a lead-through method of programming for industrial robots. The goal is to automatically reproduce 6DoF trajectories of a tool wielded by a human operator demonstrating a motion task. We present a novel motion-tracking system built around the HTC Vive pose estimation system. Our solution allows complete automation of the robot teaching process. Specific algorithmic issues of system calibration and motion data post-processing are also discussed, constituting the paper's theoretical contribution. The motion tracking system is successfully deployed in a pilot application of robot-assisted spray painting.
Keywords: Robotics; pose estimation; Motion; motion tracking; Humans; HTC Vive; trajectory planning; pohyb těles; lidé; kalibrace; Calibration; industrial robots; motion control; collaborative robotics; lead-through programming; spray coating; robotika